"The song helps us to build and to live": the role and functions of the ethnic song in Moscow Chuvash and Mari diasporic groups - Marina V. Kutsaeva (Publishing house "Sreda", 2023)
The paper studies the role and functions of songs in an ethnic language in the life of representatives of the internal diaspora. The article is based on the results of sociolinguistic surveys conducted in Chuvash and Mari diasporas of the Moscow region in 2014-2017 and 2019-2021, respectively. The researcher employed the following sociolinguistic methods: direct observation, participant observation, structured interviews of respondents, documentary recording of responses, statistical data analysis. One of the blocks in the sociolinguistic questionnaire included such aspects as the language - in - culture and ethnic culture maintenance in the context of the vitality of ethnic language. Ethnic culture, along with the ethnic language, is one of the key markers of ethnic identity in both samples. As the results of the survey demonstrate, songs in Mari or Chuvash occupy a significant place in the respondents' life. Several functions of the ethnic song were identified: adaptation to new living conditions; co-optation of new members (i. e., through cultural ethnic events); creative self-realization; language learning (i. e., ethnic songs used for educational purposes in language courses); initiation into language and culture for new speakers of Chuvash and Mari. The role of ethnic song in the revitalization of the language has been equally determined.